Exploration, Challenges, and Benefits of Implementing Management Accounting Information Systems in Private Universities: Case Study at Universitas ‘Aisyiyah Yogyakarta - Mawarti, Anggis; Rizal Yaya (Journal of Accounting and Investment, 2025)
Research aims: This research explores the implementation of the Management Accounting Information System (SIAM) in Private Higher Education Institutions (PHEIs) , focusing on its benefits, challenges, and potential solutions to enhance system effectiveness. A case study was conducted at Universitas 'Aisyiyah Yogyakarta to investigate how SIAM contributes to operational efficiency and financial decision-making . Design/Methodology/Approach: This study employs a qualitative research approach , using in-depth interviews with key stakeholders. Research findings: The findings indicate that while SIAM has significantly improved financial transparency and operational efficiency , several challenges persist, including internal limitations , such as insufficient human resource capacity in system operation , and external constraints , particularly rigid regulatory frameworks . Theoretical contribution/ Originality: To address these challenges , enhanced training programs, system integration, and diversified funding strategies are critical for optimizing SIAM implementation in private higher education institutions. Practitioner/Policy Implication : The results of this study provide important implications in the field of cyber security, especially in the management of Management Accounting Information Systems (SIAM) in Private Universities (PTS). Research limitation/Implication : This study has not explored in depth the technological aspects of system security, such as the risk of cyberattacks and their mitigation in the implementation of SIAM. This aspect is important considering the increasing threat of data security in financial information systems. Keywords : Accounting Information System, Operational Efficiency, Decision-Making, Private Higher Education Institutions, Financial Management.